Optimasi Proses Produksi Biodiesel Dari Sawit Off Grade Menggunakan Katalis Zeolit Alam Teraktivasi Pada Tahap Transesterifikasi - Heriza Saputri; Zuchra Helwani; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Oil-palm off grade is a source of vegetable oil that unmaximum utilization from the rest of the sorting in Crude Palm Oil (CPO) factory. The availability of oil-palm off grade is about 7-10% of a CPO factory with capacity of 30 tons per hour. This research aims to produce biodiesel from oil-palm off grade with two-stage reaction (esterification and transesterification) using activated natural zeolite catalysts in transesterification reaction. The other aims of this research is to study the influence of the reaction temperature (50, 60, 70°C), the molar ratio methanol : oil (6:1, 8:1, 10:1), and catalyst concentration (1, 3, 5%-wt) to yield of biodiesel and also to predict the optimum of proccess condition that give maximum yield. Natural zeolite is modificated by impregnation with 75% KOH solution and calcined at 450°C for 4 hours. The highest yield of biodiesel is 92,04% at the reaction temperature of 60°C, the molar ratio of methanol : oil 8:1, and 3%-wt catalyst concentration.Keywords : oil-palm off grade, biodiesel, natural zeolite modificated, response surface methodology, transesterification